Composition and Structural Characteristics of Rhizosphere Microorganisms of Polygonum sibiricum (Laxm.) Tzvelev in the Yellow River Delta - Liping Zhao; Shuai Shang; Dongli Shi; Hui Xu; Jun Wang (Diversity, 2022)
The Polygonum sibiricum (Laxm.) Tzvelev, an important herbal species used to protect seawalls, has a solid resistance to salinity and alkali and can grow on alkali spots in saline–alkali soils. So far, the composition, population, and characteristics of its rhizosphere biological community related to the adaptation salt–alkali environment were still unknown. In the present study, rhizosphere and non-rhizosphere soil samples from the P. sibiricum on Chenier Island were collected. High-throughput sequencing was conducted to obtain the structural diversity of rhizosphere microbial communities. Our results showed that the dominant bacteria groups in the rhizosphere and non-rhizosphere were Proteobacteria, Actinobacteriota, Gemmatimonadota, and Actinobacteriota. The dominant fungi groups in the rhizosphere and non-rhizosphere soil samples were Ascomycota, Basidiomycota, Chytridiomycota, and Mortierellomycota. The results of the ASVs (amplicon sequence variants) showed that fungi have more ASVs in common. The PERMANOVA analysis showed that the bacteria among different groups were significantly different. The PCoA (principal coordinates analysis) study also showed that the structures of the bacterial and fungal communities between the rhizosphere and non-rhizosphere were distinct. Function results showed that the relative abundance in COG (Clusters of Orthologous Groups of proteins) functional annotation was significantly different between the two groups. In addition to the general function prediction and carbohydrate transport and metabolism, the COG of the non-rhizosphere was higher than that of the rhizosphere. Our findings benefited the knowledge for studying and conserving the molecule-level adaptive mechanisms of P. sibiricum.